Deep characterization of individual brain-phenotype relations using a multilevel atlas. (August 2021) - Jockwitz, Christiane; Bittner, Nora; Caspers, Svenja; Amunts, Katrin
Highlights: Multimodal profiling deciphers inter-subject variability at individual level. Heterogeneous individual cognitive, lifestyle, and atrophy profiles. Deep characterization of five older males being at risk for dementia as a use case. Multilevel atlas information revealed (dis-)similarities of atrophied brain regions. Personalized neuroscience requires integration of multifactorial/multilevel data. Abstract : Population neuroimaging allows for extracting general principles of brain-phenotype relationships. Capturing individual brain-behavior profiles in groups with pronounced inter-individual variability, like the older adult population, however, remains challenging. Therefore, deep characterization is required to link multilevel brain, cognitive and lifestyle data. We here proposed a use case of five older males scoring low on a dementia screening test. We showed quite heterogeneous individual cognitive, lifestyle and grey matter atrophy profiles. Integrating additional regional genetic, molecular and connectional data using a multilevel atlas framework revealed (dis-) similarities between the atrophied brain areas, thereby helping to explain the individual phenomena and emphasizing the need for integrating multifactorial and multilevel information on the way toward individualized predictions.